1990
DOI: 10.1038/eye.1990.50
|View full text |Cite
|
Sign up to set email alerts
|

Decreased choroidal blood flow associated with retinitis pigmentosa

Abstract: The intraocular pressure pulse has been measured and used to evaluate the ophthalmic arterial pressure and the ocular pulsatile blood flow in 13 retinitis pigmentosa patients and ten similar aged healthy volunteers. The light sensitivity thresholds of the central fields of all persons were recorded using the Heijl-Krakau automated perimeter. The mean pulse amplitudes of 1.2 +/- 0.2 (26) and 2.3 +/- 0.25 (20) mmHg in the affected and in the control groups respectively differed significantly (p less than 0.001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 19 publications
(1 reference statement)
5
73
1
1
Order By: Relevance
“…Impaired oxygenation and a reduced nutrient supply may thus contribute to the reduction in retinal and choroidal blood flow. Reductions in retinal and choroidal circulation and volume have previously been shown to occur in hereditary retinal disorders and in animal models of disease (4,14,15) . Consequently, the choroidal thinning observed in our patients may be a manifestation of decreased choroidal blood flow and may indicate reduced oxygen dependence in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired oxygenation and a reduced nutrient supply may thus contribute to the reduction in retinal and choroidal blood flow. Reductions in retinal and choroidal circulation and volume have previously been shown to occur in hereditary retinal disorders and in animal models of disease (4,14,15) . Consequently, the choroidal thinning observed in our patients may be a manifestation of decreased choroidal blood flow and may indicate reduced oxygen dependence in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The choroidal vessels reveal a marked periadventitious fibrosis [22]with choriocapillaris hyalinosis [23, 24]. Many hemodynamic studies carried out in RP have demonstrated a reduction in blood flow at a choroidal [15, 16]and retinal level [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic studies have demonstrated that RP is associated with a reduction in retinal and choroidal blood flow [14, 15, 16]. Retinal hemodynamic impairment is also present in early stages of RP and various hypotheses have been advanced as to its cause [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…5 It has been clinically applied to investigate in various ocular diseases including glaucoma, 6,7 age-related macular degeneration, 8,9 diabetic retinopathy, 10,11 choroidal melanoma, 12 and retinal pigmentosa. 13 Graves' disease (GD) is an autoimmune disorder characterized by hyperthyroidism, diffuse goitre, ophthalmopathy, and rarely, dermopathy. One hypothesis for the pathogenesis of Graves' ophthalmopathy (GO) is that the immune response to thyroidstimulating hormone (TSH) receptor-like protein in orbital connect tissue initiates cytokine formation, promoting production by orbital fibroblasts of hydrophilic glycosaminoglycans, resulting in increased osmotic pressure, extraocular muscle volume, fluid accumulation, and clinical ophthalmopathy.…”
Section: Introductionmentioning
confidence: 99%